Ascorbic Acid Prevents Lipid Peroxidation by Sparing Nitric Oxide in Fibroblast Cells - Balabanli, B.; Bircan, F.; Pala, E.; Alem, N.; Ebegil, M.; Coskun, S. (Asian Journal of Chemistry, 2010)
As an antioxidant, ascorbic acid's primary role is to neutralize free radicals and nitric oxide is an effective chain-breaking antioxidant in free radical-mediated lipid peroxidation. The goal of the present study was to determine the interaction between ascorbic acid and nitric oxide as cellular antioxidants especially where nitric oxide acted as an antioxidant for H2O2 induced lipid peroxidation in mouse fibroblast cells. All experiments were carried on mouse fibroblast cell line in five groups: (1) control (2) L-NAME (100 nM) (3) ascorbic acid (500 μM) + L-NAME (4) H2O2 (1mM) (5) ascorbic acid + H2O2. Nitrate and nitrite levels in the samples were determined spectrophotometrically, based on the reduction of nitrate to nitrite by VCl3 and Griess reaction. Malondialdehyde and ascorbic acid levels were determined by HPLC. The present findings show that nitric oxide acts as an effective chain-breaking cellular antioxidant in free radical-mediated lipid peroxidation and ascorbic acid both directly and through sparing of nitric oxide protects cells against oxidant stress.